Level of Knowledge of Private Teachers on Outside Class Activities in Elementary School - Ali, Agung Kusumah; Fauzi, Riza Sukma; Prabowo, Indra (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
Outdoor education consists of activities that take place after school and include classroom play, visiting parks, fishing and farming communities, camping, and adventure sports. The purpose of what the researchers did was to find out the Knowledge Level of Physical Education Teachers on Outdoor Activities in Elementary Schools. The survey method was used in this study. The population of this study were all elementary school physical education teachers in Majalengka Wetan District, Majalengka Regency, totaling 22 people. The total sampling method used in this study, means that the entire population was selected to be sampled, namely 22 Physical Education teachers spread across 13 elementary schools. Based on the results of data processing and analysis, the results were obtained, namely the high group of 2 respondents or 9.09% of the total Physical Education teachers, and the very high category of 20 respondents or 90.91%. The average score of the instrument for overall knowledge about ALK was 87.96, falling between 80 and 100, so the researchers could conclude that the level of knowledge of elementary school sports and health physical education teachers in Majalengka Wetan District is related to activities outside the classroom as a whole including on very high category